Impact of green initiatives on perceived image and behavioural attitudes of consumers: Empirical evidence from hospitality industry - Baksi, Arup Kumar (Gyan Management Journal, 2014)
With the growing consciousness regarding the detrimental effects of global environmental turbulence, consumers are willingly reorienting their preferences towards consuming eco-safe products/services, more popularly nomenclated as ’green products/services’. Industries have also identified this shift and are not only redesigning their products/offers but also projecting themselves as ’green firms’. The hospitality and tourism industry is no different. This study empirically attempts to investigate the possible causal impact of green marketing initiatives on the perceived image of restaurants and its subsequent influence on the behavioural intentions of the consumers. Four tourist destinations in West Bengal, India, were identified for the study and eight restaurants were surveyed. For the data analysis, a number of multivariate statistical procedures and structural equation modeling were applied. The results revealed a significant correlation between the variables under study with perceived consumer effectiveness playing a critical role in segmenting consumers on the basis of their affinity to greenness as an element to perceive restaurant image. The study has future scopes where demographical effects and price-sensitivity may be tested.